Scale‐dependent effects of coppicing on the species pool of late successional beech forests in the central Apennines, Italy. Issue 3 (2nd June 2016) - Campetella, Giandiego; Canullo, Roberto; Gimona, Alessandro; Garadnai, Janos; Chiarucci, Alessandro; Giorgini, Daniele; Angelini, Elia; Cervellini, Marco; Chelli, Stefano; Bartha, Sandor
Abstract: Question: We compared active and abandoned beech coppices in terms of: (1) structural features, (2) total, understorey and overstorey plant diversity across spatial scales, and (3) species richness of beech forest specialist species. Location: Central Apennines, Italy. Methods: We applied a multi‐scale approach, working at fine scale (management unit) and at a coarser scale (forest patch). Two forest patches were selected according to management regimes (active coppicing, 1–40 yrs; abandoned coppicing, >40 yrs) in each of the two study areas (Bolognola and Ussita). Within each forest patch, 20 stands were sampled in 20 m × 20 m plots, for a total of 80 sampling units. Results: We found that the height of standards and number of dominant trees were negatively correlated with the total number of species. At the plot scale, the number of beech specialist species was significantly higher in abandoned plots. At the forest patch scale, the number of species in Bolognola was markedly higher in the actively coppiced forest than in the abandoned one, while the opposite result was found at Ussita. Regarding the beech specialist species richness, the abandoned forest at Ussita showed higher richness than the coppiced forest, while in Bolognola we found the opposite. The managed forest hosted more overstorey species than the abandoned one in both areas. Surprisingly, at forest patch scale in Bolognola, the total beech specialist species richness was higher in the coppiced plots than in the abandoned ones. The species assemblages were more similar between patches having different management regimes within the same area, than between patches having the same management regime across different areas. Conclusions: This material provides a novel contribution to the study of species diversity patterns in this forest system, suggesting the importance of a multiple scale approach in forest diversity studies. The beech specialist species can largely persist in a heterogeneous coppice landscape, where abandoned stands are mixed with stands under regular coppicing. The results can link current knowledge about beech coppice diversity on the landscape scale with that on the plot scale, and thus help guide new conservation planning. Abstract : The present study highlights the importance of a multiple scale approach in studying the effect of forest management on diversity. More than the management itself, the landscape heterogeneity seemed to influence the species richness at the plot scale, and the beech specialist species richness at the forest patch scale.